Melanin and Vitamin D: Unravelling the Mechanism and Coalition of Two Archaic Biomolecules in Human Evolution and Health - Maitra, Sumit; Bose, Arkopala; Chatterjee, Diptendu; Bandyopadhyay, Arup (Dermatology Review/Przegląd Dermatologiczny, 2025)
Melanin and vitamin D share a unique relationship. Human skin pigmentation has changed throughout the course of evolution to provide protection from intense ultraviolet radiation (UVR) while still allowing for cutaneous vitamin D synthesis. Vitamin D is essential for maintaining human health, and its synthesis occurs in the skin upon exposure to ultraviolet B radiation. Moreover, when isolated human populations migrated to radically different climatic environments with exceptionally low or high UVB exposure, pigmentation phenotypes evolved repeatedly as a result of distinct genetic processes. Rapid changes in migratory patterns and lifestyle factors further contributed to variations in human skin pigmentation and, together with environmental influences, led to vitamin D deficiency. Against this backdrop, the present review aims to untangle the intertwined roles that two ancient biomolecules, melanin and vitamin D, have played in human evolution and health.